SISTEM INFORMASI PENJUALAN TIKET KERETA API ONLINE BERBASIS WEB PADA STASIUN CEPU (Information Technology and Telematics, 2013)
PT.  Railways  is  the state-owned  rail  transport  service organized include passenger and freight,  for the people who want to make a purchase train tickets, do not have to come to the train station  shoppers can make purchases through outlets  which have cooperated with PT. Train with online services and websites PT. Railway. Media untapped by PT. Railway is the use of the internet to sell train tickets online. Development  of train  ticket  sales  system  based  WEB aims to improve services and enable customers to make a purchase train tickets without having to come directly to the train station, through  the outlets that have been provided and cooperate with PT. Railways, have online websites to PT. Railway Stations particularly in Cepu. Keywords: information systems, sales, train tickets, web, Cepu Station.